Ag nanoparticles effect on BaTiO3-Graphite-AC/Aluminum foil symmetric supercapacitor. (July 2020) - Suryani, S E I; Ristanti, I; Diantoro, M; Wisodo, H; Taufiq, A; Mufti, N
Abstract: Many supercapacitor studies focus on materials that are inflexible and have low specific capacitance. The addition of low dimension metals such as silver nanoparticles (AgNP) into the BaTiO3 -Graphite-Activated Carbon (AC)/Aluminum foil showed a change in structure and morphology. The AC and graphite are generally used as necessary materials for supercapacitors. Adding AgNP is expected to increases the general mobility and specific capacitance of BaTiO3 -Graphite-AC/Aluminum foil. In this study, we report the effect of AgNP into Graphite-AC-BaTiO3 /Al foil symmetric supercapacitors. In the first step, we prepared nanocomposite comprises (x)AgNP-graphite-AC-BaTiO3 . The dense solution then deposited on to clean aluminum foil as an electrode. The symmetric supercapacitors were sandwiched using two electrodes separated by a separator and electrolyte. It is shown that the crystal structure and morphology change with the addition of AgNP. The Optimum capacitance of Ag-BaTiO3 -Graphite-AC/Aluminum Foil supercapacitor obtained from LCR meter of 1.9×10 −5 F/g and dielectric constant of 1.03×10 6 . The cyclic voltammetry test for three-electrode systems produces a specific capacitance of 8.95 F/g and 0.83 F/g for testing two electrode systems. We obtained that the increase of AgNP increases the specific capacitance of the electrode and supercapacitor to the optimum at 0.06 g Ag.